Pembuatan Website untuk Jendela Informasi dan Publikasi Pemerintahan Desa Cijengkol – Serangpanjang - Arifin Bustomi; Cri Tanjoeng Kupala Respatiningrum Mocodompis; Dewi Puspitarini Larasati; Sulistiawati, Sulistiawati; Pagi Muhammad (Yayasan Literasi Sains Indonesia, 2024)
The public service information system is a variety of storage operations and management of communication information mechanisms from organizers to public addresses and vice versa as well as in direct word-of-mouth communication. The study in this research uses the theory of CMC (Computer Mediated Communication), as a format that is applied in the form of reading-based communication similar to document messages. The application method in community service is contained in the creation of the Cijengkol Village Website by utilizing the Wix platform as the basis for building the Cijengkol Village government Website with various stages associated with the Waterfall method. In addition, the initial phase of making this Website is by conducting discussions, creating details of the content, collecting databases, and designing the Website concept. The result of this research is that the Website has been handed over to the Cijengkol Village Government. This update can be seen from the profile photos of all village officials, surveys and documentation of some locations in Cijengkol Village, to ensure the completeness of administrative data. This handover is accompanied by knowledge transfer, especially to operators that will managing the Website.